This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Nice way, I didn't notice the angles doubling so I used,
cos
(
θ
)
cos
(
6
0
∘
−
θ
)
cos
(
6
0
∘
+
θ
)
=
4
cos
(
3
θ
)
This is Morrie's Law (so called by Richard Feynman) divided by 2. The answer is 1 6 1 = 0 . 0 6 2 5
Problem Loading...
Note Loading...
Set Loading...
Let x = cos ( 2 0 ∘ ) cos ( 4 0 ∘ ) cos ( 8 0 ∘ ) . Then using the identity 2 1 sin ( 2 x ) = sin ( x ) cos ( x ) we see that
x sin ( 2 0 ∘ ) = 2 1 sin ( 4 0 ∘ ) cos ( 4 0 ∘ ) cos ( 8 0 ∘ ) = 4 1 sin ( 8 0 ∘ ) cos ( 8 0 ∘ ) = 8 1 sin ( 1 6 0 ∘ ) = 8 1 sin ( 2 0 ∘ )
since sin ( y ) = sin ( 1 8 0 ∘ − y ) . Thus x = 8 1 , and so x cos ( 6 0 ∘ ) = 8 1 ∗ 2 1 = 1 6 1 = 0 . 0 6 2 5 .